1998
DOI: 10.1002/j.1552-4604.1998.tb04452.x
|View full text |Cite
|
Sign up to set email alerts
|

Analgesic Dose‐Response Relationship of Ibuprofen 50, 100, 200, and 400 mg after Surgical Removal of Third Molars: A Single‐Dose, Randomized, Placebo‐Controlled, and Double‐Blind Study of 304 Patients

Abstract: The purpose of this single-dose, randomized, placebo-controlled, and double-blind study was to evaluate the analgesic dose-response relationship of 50-mg, 100-mg, 200-mg, and 400-mg doses of ibuprofen after third molar surgery. Patients were instructed to take a single dose of either placebo or 50 mg, 100 mg, 200 mg, or 400 mg of ibuprofen when the postoperative pain was moderate to severe. Acetaminophen 500 mg was used as a rescue medication. Pain intensity, pain relief, and any possible adverse events were r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
32
1
4

Year Published

1999
1999
2018
2018

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 49 publications
(40 citation statements)
references
References 19 publications
3
32
1
4
Order By: Relevance
“…This study found that for the 200 mg/30 mg combination starting treatment with two tablets is more efficacious than with a single tablet, irrespective of symptom score or of analytical approach being applied. This is in line with findings from previous studies comparing the efficacy of 50‐400 mg ibuprofen25 or in meta‐analyses of ibuprofen studies in analgesic indications, demonstrating an increased efficacy with higher doses in the 200‐800 mg dose range 26. It is also in line with dose‐ranging studies with 15‐180 mg pseudoephedrine effects on nasal airway resistance 19.…”
Section: Discussionsupporting
confidence: 90%
“…This study found that for the 200 mg/30 mg combination starting treatment with two tablets is more efficacious than with a single tablet, irrespective of symptom score or of analytical approach being applied. This is in line with findings from previous studies comparing the efficacy of 50‐400 mg ibuprofen25 or in meta‐analyses of ibuprofen studies in analgesic indications, demonstrating an increased efficacy with higher doses in the 200‐800 mg dose range 26. It is also in line with dose‐ranging studies with 15‐180 mg pseudoephedrine effects on nasal airway resistance 19.…”
Section: Discussionsupporting
confidence: 90%
“…Eleven studies had 40 or more participants in both treatment arms Forbes 1991a;Hersch 1993b;Jain 1986;Kiersch 1993;Medve 2001;Mehlisch 2002;Nelson 1994;Schou 1998;Seymour 2000;Wahl 1997) (Analysis 3.5.1). The proportion of participants with at least 50% pain relief was 49% (553/1126) for ibuprofen 200 mg, and 10% (80/827) for placebo; the RB was 4.6 (3.7 to 5.6), and the NNT was 2.5 (2.3 to 2.8).…”
Section: Ibuprofen 200 Mg: (Analysis 35)mentioning
confidence: 99%
“…Nineteen studies had 40 or more participants in both treatment arms (Bakshi 1994;Cheung 2007;Cooper 1977;Cooper 1989;Hill 2001;Mehlisch 1990;Mehlisch 1995;Mehlisch 2002;Morrison 1999;Schou 1998;Seymour 1998;Edwards 2002;Van Dyke 2004;Zelenakas 2004) (Analysis 4.5.1). The proportion of participants with at least 50% pain relief was 54% (1000/1842) for ibuprofen 400 mg, and 12% (152/1244) for placebo; the RB was 4.4 (3.8 to 5.2), and the NNT was 2.4 (2.2 to 2.6).…”
Section: Ibuprofen 400 Mg: (Analysis 45)mentioning
confidence: 99%
See 2 more Smart Citations